Efektivitas Penggunaan Modul Pembelajaran Berbasis Kontekstual Pada Bidang Keahlian Bisnis Dan Manajemen Di Sekolah Menengah Kejuruan (SMK): Literature Review - Hiddiyatul Islami; Armiati Armiati (Jurnal Ecogen, 2020)
Contextual based learning modules in the areas of business and management expertise in Vocational High School (SMK) are important to be used as a teacher’s guide in teaching and as a source of learning for students in the learning process. The effectiveness of the use of this module can be generated in the development of contextual-based learning modules in the areas of expertise in AKL, BDP, and OTKP. The method used in writing this article uses the literature review method, the source of which was obtained on the Google Schoolar website with the issue of the past 8 years. From the 10 articles, it was found that the development of contextual-based learning modules in the field of business management expertise was very effectively used in the learning process by using the ADDIE, 4-D, and Borg and Ball development models. Then in its use this contextual based learning module is feasible to use in the learning process both in the classroom and learning independently at home. So, the existence of contextual based modules is able to make students have critical thinking skills in connecting teaching material or concepts that have been received with their application in real life in their environment.Keywords: effectiveness, learning modules, contextual